BIMG-19. 18F-FLUCICLOVINE PET/CT TO DISTINGUISH RADIATION NECROSIS FROM TUMOR PROGRESSION IN BRAIN METASTASES TREATED WITH STEREOTACTIC RADIOSURGERY: A PROSPECTIVE PILOT STUDY. (25th March 2021) - Tom, Martin
Abstract: PURPOSE: To estimate the accuracy of 18 F-Fluciclovine PET/CT in distinguishing radiation necrosis (RN) from tumor progression (TP) among patients with brain metastases (BM) having undergone prior stereotactic radiosurgery (SRS) who presented with a follow-up MRI brain (with DSC-MR perfusion) which was equivocal for RN versus TP. METHODS: Within 30 days of equivocal MRI brain, subjects underwent 18 F-Fluciclovine PET/CT on a Siemens Biograph mCT scanner with a 10 mCi bolus dose immediately prior to PET. Data were collected in list mode for 25 minutes post-injection and were reconstructed as a static image of data 10–25 minutes post-injection, and as a dynamic series of four 5-minute frames between 5–25 minutes post-injection. Quantitative metrics for each lesion were documented including SUVmax, SUVmean, SUVpeak, and normal brain SUVmean. Lesion to normal brain ratios were calculated. The reference standard was clinical follow-up with MRI brain (with DSC-MR perfusion) every 2–4 months until multidisciplinary consensus (or tissue confirmation) for diagnosis of RN versus TP. RESULTS: From 7/2019-11/2020, 16 of 16 planned subjects enrolled and underwent 18 F-Fluciclovine PET/CT for evaluation of 21 brain lesions. Primary histology included NSCLC (n=7), breast (n=5), melanoma (n=3), and endometrial (n=1). Ranges of quantitative metrics were: SUVmax, 2.18–12.1; SUVmean, 1.16–7.37; SUVpeak, 1.06–5.14; normal brain SUVmean, 0.19–0.50; SUVmax/normal ratio, 7.5–45.4; SUVmean/normal ratio, 4.2–26.3; and SUVpeak/normal ratio, 3.9–26.4. Among the patients 10 patients with 12 lesions who completed follow up, estimates of the area under the receiver operating characteristic curve for SUVmax, SUVmean, and SUVpeak were: 0.93, 0.93, and 0.82, respectively. CONCLUSION: In this population, 18 F-Fluciclovine PET/CT favorably produces a wide range of lesion quantitative metric values, low uptake in the normal brain, and promising accuracy to distinguish RN from TP. Completion of follow-up for all patients is required. Phase II and III studies are under development.